SHOULD INDONESIAN FISHERY POLICIES BE NAVIGATED TOWARDS THE INHERENT WEALTH OF FISHERIES OR SMALL-SCALE FISHERMENâS WELFARE? - NADIA, Nidha (PPI Dunia, 2018)
The marine fishery policies have been challenged by splitting objectives in the fishery management directed towards the inherent wealth of fisheries or the small-scale fishermenâs welfare. This research thus investigated the marine fishery policies in Indonesia, with a particular observation on the small-scale fishermenâs livelihood on the north coast of Jakarta. The objectives of the study include comprehending and analysing the rationale, potential, challenges, and the impact of the Indonesian fishery policies in terms of the multidimensional global challenges of sustainability, and that of contextual challenges of fishermenâs livelihood. This research primarily utilised a case study on north coast of Jakarta and secondary resource in the form of literatures on Indonesian fishery policies. The data collected are constructed using the approach of fishery management objectives towards wealth or welfare orientation. The result indicates that in spite of the tendency of divided fishery management approach to wealth or welfare, the global fishery policies and Indonesian fishery policies in particular cannot distinctly separate the two objectives, which results in multidimensional fishery policies with interwoven targets. Task delegation from the central government to the regional government for small-scale fishermenâs livelihood affairs is then implemented; meanwhile the central government pursues a bigger ambition towards sustainable, prosperous, and sovereign fishery. Additionally, the research argues that small-scale fishermenâs increasing consciousness towards the importance of the sustainability of fishing has shed some light on the cooperation between the government and the small-scale fishermen in programmes that can both improve small-scale fishermenâs livelihood and generate the inherent wealth of fisheries.